Solitary Endobronchial Papilloma with Malignant Transformation and Concomitant TB Infection: Case Report and Literature Review - Mohammed Al Ghobain (Case Reports in Pulmonology)
We are reporting a case of solitary endobronchial papilloma located in posterior segment of the left upper lobe of the lung with malignant transformation and negative human papilloma virus (HPV) strains in a 40-year-old Saudi nonsmoker man. The patient had a concomitant tuberculosis (TB) infection. The patient received appropriate treatment in the form of anti-TB medication and surgical resection of the squamous cell carcinoma followed by chemotherapy. There was no evidence of tumor recurrence, resulting in a complete cure. We are reporting the case as well as a literature review related to the topic.